Duration of Latency Period and Histologic Chorioamnionitis in Patients With PPROM From 24 to 32 Weeks [24Q]. (May 2016) - Patel, Krunal; Williams, Shauna; Apuzzio, Joseph; Bilinski, Robyn T.; Guirguis, George
Abstract : INTRODUCTION: The study objective was to determine if rates of histologic chorioamnionitis (HC) increased with longer latency periods. METHODS: This was a retrospective cohort study at a single institution from 1/1/2001 to 12/31/14 of patients admitted for conservative management with PPROM between 24 0/7 to 32 6/7 weeks. Patient were excluded if they were not a candidate for expectant management, multifetal gestation, HIV positive, delivered prior to hospital day 2 or did not have placental pathology results available. Patients were grouped by days from admission to delivery and rates of HC were compared. Mann-Whitney, Chi-square and Fisher's exact tests were used. RESULTS: 143 patients were included, 97 (68%) had HC. Median gestational age at time of PPROM was lower in the HC group (28 compared to 30 weeks, P =.004). The median latency period with and without HC were 6 (range 2–36) and 9 days (range 2–53), respectively ( P =.047). For the group with a latency of 2–7 days, the rate of HC was 75%, similar to those who delivered from 8–14 days (70%, P =.75). HC in patients who delivered after 14 days was 42%, lower than the day 2–7 group ( P =.0045). Clinical chorioamnionitis was similar between the two groups (HC 17.4%; no HC 21.6%, P =.66). The latency period did not differ in patient with and without clinical chorioamnionitis. CONCLUSION: There was no increase in histologic chorioamnionitis as the latency period increased in this cohort. Although the overall rate is high, this data does not suggest a specific time point when delivery can be recommended.